Haematological and anthropometric profiles and their relationship among university rugby athletes prior to an intervarsity tournament - Yaacob, Azhar; Nurdin, Armania; Marthuan @ Che Wan, Siti Zubaidah Nur Bt; Salihan, Safuraa (Springer Science and Business Media Deutschland, 2024)
Anthropometry values were commonly used to predict athletic performance in a broad range of sports, while haematological profiles were rarely used. This study aimed to describe the haematological and anthropometric profiles among university rugby athletes and assess the correlation between them. A total of 24 university rugby athletes (13 males and 11 females) participated in this study. Anthropometry parameters used in this study were height, weight, Body Mass Index (BMI), body fat percentage, and skeletal muscle mass. Haematology parameters taken are Red Blood Cells (RBC), Red Cells Distribution Width (RDW), Haemoglobin (HB), Pack Cells Volume (PCV), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin Concentration (MCHC), platelets, White Blood Cells (WBC), and a few types of WBC. The study was conducted during the preparation period for the intervarsity tournament. Anthropometry comparisons between male and female athletes show significant differences in height, weight, BMI, body fat percentage, and muscle mass. Male athletes display higher measurements compared to female athletes, except for body fat percentage. For haematological parameters, HB, RBC, RDW, PCV, MCH, MCHC, and lymphocytes show significant differences between male and female athletes. Pearson correlation analysis on male athletes shows a positive relationship between muscle mass and HB, RBC, and PCV, while body fat percentage shows a negative relationship with HB and PCV. Anthropometry is known as an indicator of athletic performance, and this study shows that there is a relationship between anthropometry and blood profile, especially haemoglobin value, in male athletes. This finding suggests that anthropometric values have a relationship with the athlete's blood profile that might benefit them.